Evaluation of Learning Guidelines During the Covid-19 Pandemic - Tran Chong; Long Hui La (Newinera Publisher, 2021)
The Covid-19 epidemic has led in significant changes across the board, particularly in the realm of education. Every level of education seems to be being 'forced' to adapt in order to accommodate students studying from home via online media. Educators are expected to be innovative in their delivery of curriculum using online learning medium. The Covid-19 epidemic is a worldwide pandemic, and the National Public Health Board has declared a national emergency. A number of preventative measures have been implemented by the government in order to avoid and reduce the spread of the virus. It is hoped that we would acquire acclimated to the existing system as a learning culture in educational institutions.